2015
DOI: 10.3233/cbm-140442
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants at 6p21.1 are associated with head and neck cancer in Chinese Han population

Abstract: Our results suggest that genetic variants at 6p21.1 may play an important role in HNC development in Han Chinese, and rs2494938 may be a candidate marker for HNC susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…Wang et al . also found that rs2494938 SNP was associated with an increased risk of head and neck cancer in a Chinese Han population [14]. We found that two additional SNPs, at rs1321311 and rs9363918, were also associated with shorter survival in LC patients.…”
Section: Discussionsupporting
confidence: 60%
“…Wang et al . also found that rs2494938 SNP was associated with an increased risk of head and neck cancer in a Chinese Han population [14]. We found that two additional SNPs, at rs1321311 and rs9363918, were also associated with shorter survival in LC patients.…”
Section: Discussionsupporting
confidence: 60%
“…Until now, evidences have confirmed the association of the polymorphism rs2285947 in DNAH11 with the higher risk of human cancers, such as ovarian cancer, head and neck cancer, lung cancer, non-cardia gastric cancer and esophageal squamous cell carcinoma [14, 26, 27]. We found that the GA/AA genotype of rs2285947 exhibited a significant association with poorer survival than the GG genotype among ESCC patients.…”
Section: Discussionsupporting
confidence: 56%